Silicate weathering and the habitability of temperate, rocky planets - Graham, RJ (2022)
Through the climate-dependence of silicate weathering, the carbonate-silicate cycle is thought to provide a powerful negative feedback on atmospheric CO2 that has maintained clement surface conditions on Earth almost continuously for 4 billion years in the face of profound environmental change. The fundamental role played by silicate weathering in sustaining long-term habitability on Earth has led to the hypothesis that sufficiently “Earth-like” exoplanets may have their climates regulated by the same process. This allows the definition of a “circumstellar habitable zone” around a star, where planets with carbonate-silicate cycling could in principle adjust CO2 to levels that prevent runaway glaciation or extreme surface warmth. This definition of the habitable zone has become a major organizing principle in exoplanetary astronomy, guiding telescope design and target prioritization. This thesis will deploy coupled models of exoplanetary climate, ocean chemistry, and silicate weathering to examine the implications and validity of the assumption that Earth-like planets can regulate their climates with silicate weathering throughout the putative habitable zone.